Optimization strategies for sports medicine services in Romania - Busneag, R.; Busneag, C. (Journal of Sport and Kinetic Movement, 2019)
The paper aims to provide solutions for optimizing the management of the national system of sports medicine in Romania.We used as a qualitative research method the structured interview, being set-up evaluation questionnaires for medical staff but also for the sport personnel. By processing the questionnaires, we were able to draw a number of conclusions concerning the specialty of sports medicine but also its network and its financing and issues of national and international research programs in sports medicine.